2015
DOI: 10.2298/vsp140408073v
|View full text |Cite
|
Sign up to set email alerts
|

Sweat rate and fluid intake in young elite basketball players on the FIBA Europe U20 Championship

Abstract: Most of the athletes start competition dehydrated, fail to compensate sweat loss during the game and continue to be dehydrated, regardless what kind of drink was used. These results suggest that hydration strategies must be carefully taken into account, not only by the players, but also by the coaches and the team doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Similar results have been reported in rugby and Australian Football, where high sweating rates led to significant hypohydration in some [ 67 , 80 ] but not all studies [ 67 , 70 ]. High mean sweating rates have also been reported in basketball [ 15 , 59 , 64 , 65 ], tennis [ 50 , 51 , 58 ], ice hockey [ 74 76 ], and beach volleyball [ 87 ]; however, mean BML was <2%, suggesting that drinking opportunities were sufficient to provide most athletes with enough fluid to offset sweat losses.…”
Section: Fluid Balance In Team Sportsmentioning
confidence: 99%
“…Similar results have been reported in rugby and Australian Football, where high sweating rates led to significant hypohydration in some [ 67 , 80 ] but not all studies [ 67 , 70 ]. High mean sweating rates have also been reported in basketball [ 15 , 59 , 64 , 65 ], tennis [ 50 , 51 , 58 ], ice hockey [ 74 76 ], and beach volleyball [ 87 ]; however, mean BML was <2%, suggesting that drinking opportunities were sufficient to provide most athletes with enough fluid to offset sweat losses.…”
Section: Fluid Balance In Team Sportsmentioning
confidence: 99%
“…Seventy five percent of young elite basketball players at the FIBA Europe U20 Championship started the tournament with a dehydration of 883 m Osmol/bm. In turn, tests involving adult NBA players during the summer basketball league revealed that 52% of tested individuals started games in the state of dehydration (USG > 1,020) [24] . During official competition in basketball the loss of fluids is significant, and can reach 2 litres per 20 minutes of the game.…”
Section: Discussionmentioning
confidence: 99%
“…Specific individual recommendations concerning the intake of fluids should be calculated based on sweat rates, sport dynamics, and individual tolerance. Some authors suggest a general rehydration protocol for basketball players: 200 mL at quarter breaks, 400 mL at half time and 100 mL at one timeout/half [24] . However, certain tests indicate the lack of appropriate supply of fluids during the game in spite of players having unlimited access to them.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] The few studies that have assessed indoor athletes have also shown that sweat rates are high and dehydration is still prevalent. 11,20,21 This has been found to be especially true in basketball players because of its intermittent nature. 21,22 Research on volleyball players is limited; the only study examining volleyball players' hydration status utilized adolescents athletes in a non-airconditioned facility.…”
Section: Introductionmentioning
confidence: 99%
“…11,20,21 This has been found to be especially true in basketball players because of its intermittent nature. 21,22 Research on volleyball players is limited; the only study examining volleyball players' hydration status utilized adolescents athletes in a non-airconditioned facility. 9 Therefore, hydration knowledge and practices of female indoor collegiate players is unknown, nor is it known if an educational intervention would be effective in improving hydration knowledge and habits.…”
Section: Introductionmentioning
confidence: 99%